Domoznanstvo in posebne zbirke v Koroški osrednji knjižnici dr. Franca Sušnika - Šuler Pandev, Simona (Knjižnica, 2005)
The Dr. Franc Sušnik Central Carinthian Library's local studies activities are presented in this article. Already as the former Ravne na Koroškem Study Library, the Dr. Franc Sušnik Central Carinthian Library has incessantly maintained its local studies collection function with planned and systematic supplementation of the book material, serial publications, special collections and exhibition activity. Today the library is the central regional library in Koroška and, as specified by the law, performs various tasks for the wider region, receives obligatory copies, purchases library material for Slovenes abroad and completes the local bibliography for Koroška abroad. Many special collections, which the library can be proud of, are the result of a many year's hard work. Formation of special collections accordingly to the kind and typology of material demands of a professional librarian also to be fully acquainted with certain elements of archival storage and museum activity. There have been great changes taking place in the field of local collection activity, as a consequence of the use of new technologies, while at the same time this work is hindered by financial troubles and deficiency of the tools needed for the input of the local collection materials into shared cataloguing. The library tends towards a unified and cooperative processing of the local studies collection materials, a good referral work and uniformed mediation of material and information. The aim is certainly to provide users with a fast, easily accessible and cheap local studies collection information.
Keywords: splošne knjižnice; Koroška osrednja knjižnica dr. Franca Sušnika; Ravne na Koroškem; domoznansko gradivo; domoznanske zbirke